Second primary head and neck cancer after Hodgkin lymphoma: A population‐based study of 44, 879 survivors of Hodgkin lymphoma. Issue 9 (8th January 2015) - Chowdhry, Amit K.; McHugh, Colin; Fung, Chunkit; Dhakal, Sughosh; Constine, Louis S.; Milano, Michael T.
Abstract : BACKGROUND: Survivors of Hodgkin lymphoma (HL) are at an increased risk of developing second malignancies. To the authors' knowledge, the risks of head and neck cancer (HNC) after HL and subsequent survival have not been thoroughly investigated. METHODS: From the US population‐based Surveillance, Epidemiology, and End Results (SEER) database for 1973 through 2011, survivors of HL who developed HNC as a second cancer were analyzed. Patients with a first primary HNC were used as a comparison group. Observed‐to‐expected ratios and summary statistics were performed on patients with HL with squamous cell carcinoma (HL‐SCC) and salivary gland cancer (HL‐SGC). The impact of HL history on overall survival was assessed using a multivariate Cox proportional hazards model. RESULTS: The observed‐to‐expected ratio for SCC among patients with HL was 1.73 (95% confidence interval [95% CI], 1.36‐2.16; P <.05), whereas it was 8.56 for SGC (95% CI, 5.82‐12.15; P <.05). Using Cox proportional hazards modeling, a history of HL was found to be an adverse prognostic factor for overall survival for SCC (hazard ratio, 1.37; 95% CI, 1.08‐1.73 [ P = .009]) but not SGC (hazard ratio, 1.21; 95% CI, 0.82‐1.79 [ P = .34]). The inferior survival of the patients in the HL‐SCC cohort appears to be attributable to more deaths from HL and other malignancies diagnosed after SCC. CONCLUSIONS: There is a significantly increased risk of salivary and nonsalivary HNC after HL, and worse survival for patients with HL‐SCC versus those with a first primary SCC. Clinicians should be aware of the risks of HNC after HL. In the absence of evidence‐based criteria, the authors recommend that survivors of HL undergo periodic head and neck examination. Cancer 2015;121:1436–1445. © 2015 American Cancer Society . Abstract : There is a significantly increased risk of salivary and nonsalivary head and neck cancer after a diagnosis of Hodgkin lymphoma. Survivors of Hodgkin lymphoma with squamous cell head and neck cancer experience worse survival outcomes.